Studi Tentang Representasi dan Prsepsi di Media Instagram Terhadap Konstruksi Seksualitas (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine how the construction of sexuality is represented and perceived through Instagram social media. As a dominant visual platform, Instagram plays an important role in shaping body image, gender, and intimate relationships that are often influenced by popular culture, media algorithms, and prevailing social norms. Using a qualitative approach and in-depth interview method with six informants, this study found that the representation of sexuality on Instagram generally reflects ideal body standards, which can cause social and psychological pressures, such as body anxiety, insecurity, and objectification. On the other hand, some users also see Instagram as a space for self-expression, empowerment, and education, especially for those who have a critical awareness of the social construction behind the content. Perceptions of ideal sexuality also vary widely, depending on the cultural background, personal experiences, and visual preferences of each user. These findings emphasize the importance of media literacy and critical reflection so that social media can become a healthier, fairer, and gender-inclusive digital space.